PENGARUH KOMITE AUDIT, REPUTASI KAP, DAN OPINI AUDIT TERHADAP AUDIT DELAY - Daeli, Sadari; Widiyati, Dian (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of the audit committee, KAP reputation and audit opinion on audit delay in non-primary consumer sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research method uses a quantitative associative design. The population used in this research is non-primary sub-consumer companies listed on the Indonesia Stock Exchange. Sample selection was carried out using the purposive sampling method. The sample used in this research was 77 non-primary consumer sub-sector companies in 2019-2022. The data method used in this research is multiple linear regression analysis, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. Significant tests include the t statistical test and f test, coefficient of determination using Eviews 12. The results of this research indicate that the audit committee has no effect on audit delay. The results of this research show that KAP reputation has an effect on audit delay. The results of this research also show that audit opinion has no effect on audit delay